2020
DOI: 10.3138/cjhs.2019-0049
|View full text |Cite
|
Sign up to set email alerts
|

Youth perspectives on sexual health education: Voices from the YEP study in Toronto

Abstract: The Youth Engagement Project (YEP) is a community-based pilot study in Toronto, Canada that we developed to better understand perspectives about and experiences of sexual health education among socioeconomically marginalized, racialized, and LGBTQ youth. We investigated: 1) what sex-related messages these young people received as they grew up, 2) how those messages affected their perspectives and sexual behaviour, and 3) their recommendations for sexual health education that meets their needs. Engaging youth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…Likewise, and preparedness to address diff erent sexual health-related top-youth (ages 13 and above) in Toronto reported that the sexuics, which may result in teachers only teaching topics they are al health topic they most frequently wanted to learn about was most comfortable with ( Balter et al, 2016 ;Cohen et al, 2004 ;healthy relationships (C ausarano et al, 2010). Y outh in these Toronto-based studies (Causarano et al, 2010;Narushima et al, 2020) also expressed wanting to receive more positive messag es and learn more about sexual pleasure. In another Canadian study, Cormier and O'Sullivan (2018 ) observed that participants (ages 18-21) retrospectively felt dissatisfied that their sexual health education had skipped over sexual pleasure as a topic.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, and preparedness to address diff erent sexual health-related top-youth (ages 13 and above) in Toronto reported that the sexuics, which may result in teachers only teaching topics they are al health topic they most frequently wanted to learn about was most comfortable with ( Balter et al, 2016 ;Cohen et al, 2004 ;healthy relationships (C ausarano et al, 2010). Y outh in these Toronto-based studies (Causarano et al, 2010;Narushima et al, 2020) also expressed wanting to receive more positive messag es and learn more about sexual pleasure. In another Canadian study, Cormier and O'Sullivan (2018 ) observed that participants (ages 18-21) retrospectively felt dissatisfied that their sexual health education had skipped over sexual pleasure as a topic.…”
mentioning
confidence: 99%
“…Research fi ndings have suggested that cess to curricula for diverse learners, such as the ' Tell It Like It Is': youth want their teachers to be trustworthy, non-judgemental, Sexual Health and Wellness Education ( Creative Options Regina and open to discussion ( Hilton, 2003( Hilton, , 2007Kimmel et al, et al, 2018 ). Th is also includes increased access to evidence-based 2013 ; Lester & Allan, 2006 ;Narushima et al, 2020 ;O'Higgins & online learning such as sexandu.ca ( Th e Society of Obstetricians Gabhainn, 2010 ). Th ese fi ndings suggest that select information and Gynaecologists of Canada, 2020 ) and t eenhealthsource.com and a safe, comfortable environment may be missing in the sexual (Pla nned Parenthood Toronto, 2020), as w ell as more community-health education experiences for some.…”
mentioning
confidence: 99%
See 3 more Smart Citations